+0  
 
0
301
1
avatar

Let f(x) = 4x + 3 and g(x) = -2x + 5. Findmc016-1.jpg

 

 


23

–17

-41

–5

Guest Mar 20, 2015

Best Answer 

 #1
avatar+87301 
+5

Let f(x) = 4x + 3 and g(x) = -2x + 5. Findmc016-1.jpg

(f o g)(5) says we want to put 5 into g and evaluate the result......then.....we want to put this result into f and evaluate that........so

g(5) = -2(5) + 5 = -10 + 5 = -5

And

f(-5)  = 4(-5) + 3 =  -20 + 3 = -17

 

  

CPhill  Mar 20, 2015
 #1
avatar+87301 
+5
Best Answer

Let f(x) = 4x + 3 and g(x) = -2x + 5. Findmc016-1.jpg

(f o g)(5) says we want to put 5 into g and evaluate the result......then.....we want to put this result into f and evaluate that........so

g(5) = -2(5) + 5 = -10 + 5 = -5

And

f(-5)  = 4(-5) + 3 =  -20 + 3 = -17

 

  

CPhill  Mar 20, 2015

12 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.